Nutritional therapy in the immediate post-liver transplant period: a discussion about the standard operating procedure (POP) 9 (Research, Society and Development, 2022)
The present study seeks to explain and discuss the available literature on nutritional therapy for patients in the postoperative period of liver transplantation, using as a base document the POP 9 of the Brazilian Company of Hospital Services (EBSERH), since this is a national reference in the execution of health services including organ transplantation. This is a narrative review of the literature carried out in January 2022, built to explain POP 9 of the Brazilian Company of Hospital Services (EBSERH). The following descriptors and their combinations were used according to the criteria of each database: “nutritional therapy”, “postoperative” and “liver transplantation”, using the term “and” as the Boolean operator. The research made it possible to identify 7 studies that will be cited in the discussion of the work. The present study can contribute to foment and enrich the knowledge about the therapy in the post-liver transplant, and through the Standard Operating Procedure POP.009 - from the EBSERH, it was possible to build a rich discussion and update on the dietary therapeutic procedures in the post-transplant period. liver transplant. According to the literature reviewed, it is possible to state that patients undergoing liver transplantation are subjected to a great clinical and nutritional challenge, from their admission to the hospital until their medical discharge. The management of its conditions is intensely delicate and the control must be rigorous in order to prevent complications that may affect the patient's prognosis.